2018
DOI: 10.1159/000493788
|View full text |Cite
|
Sign up to set email alerts
|

Can Functional Polymorphisms in <b><i>VEGF</i></b> and <b><i>MMP</i></b> Predict Intraventricular Hemorrhage in Extremely Preterm Newborns?

Abstract: Background: The pathophysiology of intraventricular hemorrhage (IVH) is multifactorial. This study attempts to identify genetic and clinical factors contributing to IVH in newborns with a focus on those born ≤28 weeks of gestation. Methods: This was a prospective study of 382 consecutive newborns admitted to the neonatal intensive care unit. DNA purification was conducted using standard methods. TaqMan SNP assays were conducted for functional polymorphisms in VEGF (RS699947, RS2010963, RS3025039, and RS1570360… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similarly, there was approximately a 3.5-fold increased risk of developing IVH in preterm infants with the GT eNOS 894G > T polymorphism of endothelial nitric oxide synthase (eNOS), a gene associated with blood flow [12]. Prasun P et al examined polymorphisms in VEGF and showed a higher prevalence of IVH in infants with GA/AA and AA/AC genotypes in VEGF RS1570360 and VEGF RS699947, respectively [36]. The fibronectin (FN1) gene has been assessed in relation to multiple disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was approximately a 3.5-fold increased risk of developing IVH in preterm infants with the GT eNOS 894G > T polymorphism of endothelial nitric oxide synthase (eNOS), a gene associated with blood flow [12]. Prasun P et al examined polymorphisms in VEGF and showed a higher prevalence of IVH in infants with GA/AA and AA/AC genotypes in VEGF RS1570360 and VEGF RS699947, respectively [36]. The fibronectin (FN1) gene has been assessed in relation to multiple disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study on 382 infants with a gestational age less than 28 weeks hospitalized in the neonatal intensive care unit analyzed 4 SNPs for VEGF polymorphisms (RS699947, RS2010963, RS3025039, and RS1570360). They established that the GA/AA genotype in VEGF RS1570360 and the AA/AC genotype in VEGF RS699947 were associated with elevated incidence rates of IVH in newborns ≤28 weeks of gestation ( p = 0.017) [ 119 ]. Additionally, a higher presence of the CC genotype for SNP VEGF RS3025039 tended to an increased incidence of IVH of principally African American newborns, and the CC genotype of VEGF RS1570360 was associated with a need for ventriculoperitoneal shunt placement surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Such findings indicate that certain fibronectin polymorphisms can have a detrimental effect on the structural integrity of the germinal matrix. Furthermore, Prasun et al [ 24 ] found that the GG in VEGF RS1570360 and CC genotypes in VEGF RS699947 were risk factors for IVH in infants less than 28 weeks old. In another study, it was found that the genotype CC of MTHFR 1298A > C gene polymorphism increased the risk of IVH by approximately 4.5 times (OR: 4.51, p < 0.03) for infants less than 32 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%